Hubungan Tayangan Channel Youtube Kimbab Family dengan Minat Belajar Bahasa Korea pada Subscribers - Haya Khalilah Ulya; Yulianti (Bandung Conference Series: Communication Management, 2022)
Abstract. Youtube is one of the popular social media that can be used to share information and entertainment. Along with the times, now YouTube can be used as a learning medium, especially language, as done by Gina Selvina and Yeon Seung Jay as content creators behind the Kimbab Family youtube channel. Both are husband and wife who have different nationalities, namely Indonesia and Korea. Most of the video content uses a combination of two languages, namely Indonesian and Korean. This study attempts to explain the relationship between the Kimbab Family youtube channel impressions and customer interest in learning Korean. In this study, it was seen from the aspect of media exposure consisting of frequency, attention and duration. The theory used is the stimulus-response theory. Quantitative research methods with a correlational approach are used in this study to test whether there is a relationship between the two variables. Data collection techniques by distributing online questionnaires to respondents. The population in this study was the Kimbab Family youtube channel subscribers, which amounted to 2,000,000 people and the Taro Yamane formula was used so that a sample of 400 respondents was obtained. The results of this study indicate that there is a very strong and unidirectional relationship or positive correlation between the Kimbab Family youtube channel shows and subscriber interest in learning Korean. Abstrak. Youtube adalah salah satu media sosial populer yang dapat digunkan untuk membagikan informasi maupun hiburan. Seiring perkembangan zaman, kini youtube dapat dimanfaatkan sebagai media pembelajaran khususnya bahasa, seperti yang dilakukan oleh Gina Selvina dan Yeon Seung Jay selaku content creator dibalik channel youtube Kimbab Family. Keduanya merupakan pasangan suami istri yang memiliki kewarganegaraan yang berbeda yakni Indonesia dan Korea. Sebagian besar konten videonya menggunakan gabungan dua bahasa yakni Bahasa Indonesia dan Bahasa Korea. Penelitian ini berusaha untuk menjelaskan hubungan antara tayangan channel youtube Kimbab Family dengan minat belajar Bahasa Korea pada subscribers. Dalam penelitian ini dilihat dari segi terpaan media yang terdiri dari frekuensi, atensi dan durasi. Teori yang digunakan adalah teori stimulus-respons. Metode penelitian kuantitatif dengan pendekatan korelasional digunakan dalam penelitian ini untuk menguji ada tidaknya hubungan antara kedua variabel. Teknik pengumpulan data dengan cara menyebarkan kuesioner online kepada responden. Populasi penelitian ini adalah subscribers dari channel youtube Kimbab Family yang berjumlah 2.000.000 orang dan digunakan rumus Taro Yamane sehingga diperoleh sampel sebanyak 400 responden. Hasil penelitian ini menunjukkan bahwa terdapat hubungan yang sangat kuat dan searah atau korelasi positif antara tayangan channel youtube Kimbab Family dengan minat belajar Bahasa Korea pada subscribers.